Perturbation and change in coral reef communities - Porter, James W. (1982)
Ninety-six percent of surveyed shallow-water Dry Tortugas reef corals died during the severe winter of 1976-1977. Data from skeletal stains indicate that death occurred during the mid-January intrusion of 14°C water onto the reef. In deeper water, community parameters such as percent cover, species number, and relative abundance showed no significant change. However, an analysis of competitive interactions at the growing edges of adjacent colonies reveals a 70% reduction in space competition during this environmental disturbance. These results can explain high variability in the growth rate of Floridian reefs and demonstrate the importance of obtaining long-term spatial information to interpret successional dynamics of complex communities.